Circulating Tumor Cell–Based Messenger RNA Scoring System for Prognostication of Hepatocellular Carcinoma: Translating Tissue‐Based Messenger RNA Profiling Into a Noninvasive Setting. Issue 2 (16th November 2021) - Lee, Yi‐Te; Sun, Na; Kim, Minhyung; Wang, Jasmine J.; Tran, Benjamin V.; Zhang, Ryan Y.; Qi, Dongping; Zhang, Ceng; Chen, Pin‐Jung; Sadeghi, Saeed; Finn, Richard S.; Saab, Sammy; et al.
Abstract : Numerous studies in hepatocellular carcinoma (HCC) have proposed tissue‐based gene signatures for individualized prognostic assessments. Here, we develop a novel circulating tumor cell (CTC)–based transcriptomic profiling assay to translate tissue‐based messenger RNA (mRNA) signatures into a liquid biopsy setting for noninvasive HCC prognostication. The HCC‐CTC mRNA scoring system combines the NanoVelcro CTC Assay for enriching HCC CTCs and the NanoString nCounter platform for quantifying the HCC‐CTC Risk Score (RS) panel in enriched HCC CTCs. The prognostic role of the HCC‐CTC RS was assessed in The Cancer Genome Atlas (TCGA) HCC cohort (n = 362) and validated in an independent clinical CTC cohort (n = 40). The HCC‐CTC RS panel was developed through our integrated data analysis framework of 8 HCC tissue‐based gene signatures and identified the top 10 prognostic genes ( discoidin domain receptor tyrosine kinase 1 [ DDR1], enoyl‐CoA hydratase and 3‐hydroxyacyl CoA dehydrogenase [EHHADH], androgen receptor [AR], lumican [LUM], hydroxysteroid 17‐beta dehydrogenase 6 [HSD17B6], prostate transmembrane protein, androgen induced 1 [PMEPA1], tsukushi, small leucine rich proteoglycan [TSKU], N‐terminal EF‐hand calcium binding protein 2 [NECAB2], ladinin 1 [LAD1], solute carrier family 27 member 5 [SLC27A5] ) highly expressed in HCC with low expressions in white blood cells. The panel accurately discriminated overall survival in TCGA HCC cohort (hazard ratio [HR], 2.0; 95% confidence interval [CI], 1.4‐2.9). The combined use of the scoring system and HCC‐CTC RS panel successfully distinguished artificial blood samples spiked with an aggressive HCC cell type, SNU‐387, from those spiked with PLC/PRF/5 cells ( P  = 0.02). In the CTC validation cohort (n = 40), HCC‐CTC RS remained an independent predictor of survival (HR, 5.7; 95% CI, 1.5‐21.3; P  = 0.009) after controlling for Model for End‐Stage Liver Disease score, Barcelona Clinic Liver Cancer stage, and CTC enumeration count. Our study demonstrates a novel interdisciplinary approach to translate tissue‐based gene signatures into a liquid biopsy setting. This noninvasive approach will allow real‐time disease profiling and dynamic prognostication of HCC.